The Implementation of the Active Learning Strategy: Practice-Rehearsal Pairs Type to Improve Students' Mathematics Learning Motivation - Perdana, Dina Novarina; Yolanda, Nela Sari; Utami, Khurnia Budi; Suriani, Teni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Learning motivation is one of the main factors determining students’ success in learning mathematics. A lack of learning motivation can cause students to be less actively involved and experience difficulties in understanding the material being studied. Therefore, it is necessary to implement learning strategies that can encourage student engagement and enhance their learning motivation. This study aims to describe the implementation of the Practice-Rehearsal Pairs active learning strategy and its effect on students’ motivation in learning mathematics. The research employed a descriptive approach with students of class XE6 as the control group and class XE8 as the experimental group at SMAN 1 Koto XI Tarusan. The experimental class was taught using the Practice-Rehearsal Pairs active learning strategy, while the control class used the conventional teaching method commonly applied by the teacher. Research data were collected through classroom observations during the learning process and the distribution of learning motivation questionnaires to students. The data obtained were then analyzed descriptively to examine differences in learning motivation between the control and experimental classes. The motivation indicators observed included student activeness, interest in participating in learning activities, perseverance in completing assignments, and students’ level of self-confidence in learning mathematics. The results of the study indicate that the implementation of the Practice-Rehearsal Pairs active learning strategy has a positive impact on students’ motivation in learning mathematics. Students became more enthusiastic, actively participated in learning activities, showed greater perseverance, and demonstrated increased self-confidence. Thus, the Practice-Rehearsal Pairs active learning strategy can be used as an alternative instructional approach to improve students’ motivation in learning mathematics.